2009
DOI: 10.1111/j.1365-294x.2009.04137.x
|View full text |Cite
|
Sign up to set email alerts
|

Species relative abundance and direction of introgression in oaks

Abstract: Successful hybridisation and subsequent introgression lead to the transfer of genetic material across species boundaries. In this process, species relative abundance can play a significant role. If one species is less abundant than the other, its females will receive many heterospecific gametes, increasing mate-recognition errors and thus hybridisation rate. Moreover, first-generation hybrids will also more likely mate with the more abundant species, leading to asymmetric introgression. These predictions have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
429
5
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 306 publications
(458 citation statements)
references
References 69 publications
23
429
5
1
Order By: Relevance
“…These populations contained not only putative F1 individuals that showed approximately 50 % admixture between two species, but also backcrossed individuals and even some individuals that showed admixture between all three parental species. Such complex patterns of hybridization are usually interpreted as evidence that hybridization has been going on for several generations (Lepais et al 2009;Thompson et al 2010).…”
Section: Hybridization In Pericallismentioning
confidence: 99%
“…These populations contained not only putative F1 individuals that showed approximately 50 % admixture between two species, but also backcrossed individuals and even some individuals that showed admixture between all three parental species. Such complex patterns of hybridization are usually interpreted as evidence that hybridization has been going on for several generations (Lepais et al 2009;Thompson et al 2010).…”
Section: Hybridization In Pericallismentioning
confidence: 99%
“…In general, sharp genetic delineation between sympatric species is not very new for the European white oak complex. Several authors have recently found strong genetic separation of species in mixed stands across the main range of coexistence of different oak species (Gugerli et al 2007;Curtu et al 2007;Lepais et al 2009). However, our results provide new evidence for strong reproductive barriers and/or selection mechanisms among European oak species that shape their ecology and evolution at the Northern range margin.…”
Section: Discussionmentioning
confidence: 99%
“…The earlier surveys of leaf morphology suggested that trees in the study population reveal great variation spanning among three species: Q. pubescens, Q. petraea and Q. robur (Celiński and Filipek 1958;Staszkiewicz 1977;Danielewicz et al 2002). However, because these species are potentially cross-fertile (Lepais et al 2009;Salvini et al 2009;Lepais and Gerber 2011), we assumed that the study population embraces all 2,200 individuals, which however can mate non-randomly due to taxonomic or other barriers (e.g. distance, flowering synchrony).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations